Penerapan Water Tepid Sponge pada Anak Usia Pra Sekolah dalam Pengelolaan Hipertermia pada Demam Typhoid: Studi Kasus: Application of Water Tepid Sponge in Preschool Children for Managing Hypertermia in Thypoid Fever: A Case Study - Toyibah; Puji Astuti, Ana (Universitas Ngudi Waluyo, 2025)
Typhoid fever presents with hyperthermia, a condition that can affect preschool children. Preschool children have an underdeveloped immune system and poor personal hygiene habits, it makes susceptible to infections such as typhoid fever, which is characterized with hyperthermia. The goal of this study is describing the application of water tepid sponges (WTS) in reducing the body temperature of preschool children with typhoid fever. This study uses a descriptive method with a case study approach of nursing process, on one preschool child with typhoid fever and hyperthermia. The intervention provided was hyperthermia management through water tepid sponge compresses for 3 days management, monitoring of changes in body temperature before and after the intervention. Data collection techniques included assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. The results of the management are that hyperthermia can be resolved, with a decrease in body temperature on the first day, the patient's body temperature before being given a water tepid sponge was recorded at 38.9°C, then decreased to 37.5°C after the procedure within 15 minutes. On the second day, the initial temperature of 38.5°C decreased to 36.9°C after being given WTS. On the third day, the patient's body temperature was 36.5°C, indicating that the body temperature had returned to normal. Suggestions for families are expected to implement the health education that has been provided by nurses, especially in carrying out water tepid sponge (WTS) compress actions at home as an independent effort in treating children when they have a fever.